Characteristics of Austrian Remedies against Enforcement and a General Analysis of their Suitability for Achieving the Objectives of Brussels I Recast - Nunner-Krautgasser Bettina (LeXonomica, 2017)
Regulation No 1215/2012 (Brussels Ia or Brussels I Recast) was another big step forward towards the establishment of a genuine European judicial area. In the wake of the Brussels I Recast, two facts have rather soon become apparent: One, several wellknown (or better: infamous) issues are sadly still unsolved. And two, some other issues have emerged. Because of the abolishment of the “exequatur procedure”, esp. the issue of remedies against enforcement, in both the Member State of origin as well as in the Member State of enforcement, has gained more importance again. Therefore this paper analysis the characteristics of Austrian remedies in enforcement and their suitability for achieving the objects of Brussels I Recast.